1997
DOI: 10.1021/np960556t
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Glycosides from Albizia julibrissin

Abstract: During the course of a study of leguminous plants, cytotoxicity was demonstrated by the crude saponin fraction of Albizia julibrissin. Following chromatographic purification, the structures of three novel saponins, julibrosides I-III (1-3), inclusive of a cytotoxic principle, were elucidated. A comparison of the cytotoxicity of julibrosides (1-3) and their prosapogenins (4-15) prepared by alkaline hydrolysis clearly indicated that both an alpha-L-arabinofuranosyl-(1-->4)-[beta-D-glucopyranosyl-(1-->3)]-alpha- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
91
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 5 publications
6
91
0
Order By: Relevance
“…In Korea, the stem bark is used in traditional medicine to treat insomnia, diuresis, asthenia, ascaricide, and confusion. Ikeda et al (1997) demonstrated that the crude saponin fraction obtained from A. julibrissin showed significant (IC 50 12.8 lg/ml) cytotoxicity against the KB cell line. Following chromatographic purification, julibrosides I-III (20-22) were obtained (Fig.…”
Section: Julibrosidesmentioning
confidence: 98%
See 2 more Smart Citations
“…In Korea, the stem bark is used in traditional medicine to treat insomnia, diuresis, asthenia, ascaricide, and confusion. Ikeda et al (1997) demonstrated that the crude saponin fraction obtained from A. julibrissin showed significant (IC 50 12.8 lg/ml) cytotoxicity against the KB cell line. Following chromatographic purification, julibrosides I-III (20-22) were obtained (Fig.…”
Section: Julibrosidesmentioning
confidence: 98%
“…The cytotoxicity profile of Julibrosides I-III (20-22) was examined against the KB cell lines (Ikeda et al 1997). Only julibroside III (22) showed significant cytotoxicity with an IC 50 value of 0.9 lM.…”
Section: Julibrosidesmentioning
confidence: 99%
See 1 more Smart Citation
“…1) Earlier phytochemical investigations on this species resulted in the isolation of saponins, [2][3][4][5] lignans, [6][7][8] phenolic glycosides, 6) triterpenes, 9) flavonoids and others. [10][11][12][13][14][15] Previously, we reported that the methanolic extract of the stem bark of A. julibrissin exerts an radical scavenging activity on 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical.…”
mentioning
confidence: 99%
“…3 This finding prompted us to prepare neosaponins carrying the original tetrasaccharide component and to examine their biological activities.…”
Section: Introductionmentioning
confidence: 99%